Evidence-Based Guidelines and Clinical Pathways in Stroke Rehabilitation—An International Perspective - Platz, Thomas (Frontiers in Neurology, 2019)
A high societal burden and a considerable increase in stroke-related disability was globally observed over the last 3 decades, and is expected to continue implying a major challenge for societies around the word. Structured multidisciplinary stroke rehabilitation reduces stroke-related disability both in older and younger stroke survivors of either sex and independent of stroke severity. In addition, there is rapidly increasing evidence to support the clinical effectiveness of specific stroke rehabilitation interventions. Evidence-based guidelines help to promote best possible clinical practice. Inherent difficulty for their provision is that it takes enormous efforts to systematically appraise the evidence for guidelines and their regular updates, if they should not be at risk of bias by incomplete evidence selection. A systematic review of the pertaining literature indicates that the currently published stroke rehabilitation guidelines have a national background and focus and represent the health care situations in high-income countries. Societies around the globe would benefit from central evidence sources that systematically appraise the available evidence and make explicit links to practice recommendations. Such knowledge could facilitate a more wide-spread development of valid comprehensive up-to-date evidence-based national guidelines. In addition, the development of genuine international evidence-based stroke rehabilitation guidelines that focus on therapeutic approaches rather than organisational issues, could be used by many to structure regional or local stroke rehabilitation pathways and to develop their resources in a way that will eventually achieve effective stroke rehabilitation. Such international practice recommendations for stroke rehabilitation are currently under development by the World Federation for NeuroRehabilitation (WFNR).